Maternal extracellular vesicles and platelets promote preeclampsia via inflammasome activation in trophoblasts - Kohli, Shrey; Ranjan, Satish; Hoffmann, Juliane; Kashif, Muhammed; Daniel, Evelyn A.; Al-Dabet, Moh'D Mohanad; Bock, Fabian; Nazir, Sumra; Hübner, Hanna; Mertens, Peter R.; Fischer, Klaus-Dieter; Zenclussen, Ana C.; et al. (Blood, 2016)
Preeclampsia (PE) is a placenta-induced inflammatory disease associated with maternal and fetal morbidity and mortality. The mechanisms underlying PE remain enigmatic and delivery of the placenta is the only known remedy. PE is associated with coagulation and platelet activation and increased extracellular vesicle (EV) formation. However, thrombotic occlusion of the placental vascular bed is rarely observed and the mechanistic relevance of EV and platelet activation remains unknown. Here we show that EVs induce a thromboinflammatory response specifically in the placenta. Following EV injection, activated platelets accumulate particularly within the placental vascular bed. EVs cause adenosine triphosphate (ATP) release from platelets and inflammasome activation within trophoblast cells through purinergic signaling. Inflammasome activation in trophoblast cells triggers a PE-like phenotype, characterized by pregnancy failure, elevated blood pressure, increased plasma soluble fms-like tyrosine kinase 1, and renal dysfunction. Intriguingly, genetic inhibition of inflammasome activation specifically in the placenta, pharmacological inhibition of inflammasome or purinergic signaling, or genetic inhibition of maternal platelet activation abolishes the PE-like phenotype. Inflammasome activation in trophoblast cells of women with preeclampsia corroborates the translational relevance of these findings. These results strongly suggest that EVs cause placental sterile inflammation and PE through activation of maternal platelets and purinergic inflammasome activation in trophoblast cells, uncovering a novel thromboinflammatory mechanism at the maternal-embryonic interface.
EVALuna2:33460